Penanganan Sampah Plastik pada Produksi Paving Block - Zainuri, Zainuri (Jurnal Teknologi Lingkungan, 2021)
ABSTRACT Efforts to handle waste are continuously carried out, starting from the lowest layer, namely households, to large factories that produce garbage every day. Waste production that is not balanced with the handlers causes waste to be a problem for the environment. One type of waste that is difficult to decompose by nature (non-biodegradable) is plastic waste, which occupies the most considerable quantity of other types of waste. Based on statistical data, the amount of non-biodegradable waste that is disposed of in the final disposal site every day in several cities in Indonesia is 6,598.23 tons/day. This study aims to calculate the reduction in plastic waste if it is used in making paving blocks. Almost all variations are included in quality D outlined in SNI 03-0691-1996. Only two variations have below the required standard, namely 10% plastic: 90% sand and 60% plastic: 40% sand. In the variation 70% plastic: 30% sand, the plastic weight needed is 796.32 kg and in the variation 80% plastic: 20% sand, the need for plastic waste drops to 793.60 kg. The variation 70% plastic: 30% sand is recommended for production because it absorbs the most plastic waste from the calculations made. This study concluded that the potential for reducing plastic waste if it is used for the production of paving blocks is 3.9816 tons/day in the job mix with a variation of 70% plastic: 30% sand. Keywords: inorganic, paving blocks, plastic, garbage Â  ABSTRAK Upaya penanganan sampah terus dilakukan mulai dari lapisan terbawah yaitu rumah tangga hingga pabrik besar yang menghasilkan sampah setiap hari. Produksi sampah yang belum berimbang dengan penanganan menyebabkan sampah masih menjadi masalah bagi lingkungan. Salah satu jenis sampah yang sulit diuraikan oleh alam (non-biodegradable) adalah sampah plastik, menempati kuantitas terbesar dari jenis sampah lainnya. Berdasarkan data statistik, jumlah sampah non-biodegradable yang dibuang ke TPA sampah setiap hari di beberapa kota di Indonesia sebesar 6.598,23 ton/hari. Penelitian ini bertujuan untuk menghitung potensi pengurangan sampah plastik apabila dimanfaatkan dalam pembuatan paving block. Hampir semua variasi masuk dalam mutu D yang digariskan dalam SNI 03-0691-1996. Hanya dua variasi memiliki kekuatan di bawah standar yang disyaratkan yaitu variasi 10% plastik: 90% pasir dan 60% plastik: 40% pasir. Pada variasi 70% plastik: 30% pasir, berat plastik yang dibutuhkan 796,32 kg dan pada variasi plastik 80%: 20% pasir, kebutuhan sampah plastik turun menjadi 793,60 kg. Dari perhitungan yang dilakukan maka variasi 70% plastik: 30% pasir yang direkomendasikan untuk diproduksi sebab menyerap paling banyak sampah plastik. Dalam penelitian ini disimpulkan bahwa potensi pengurangan sampah plastik jika dimanfaatkan untuk produksi paving block adalah sebesar 3,9816 ton/hari pada job mix dengan variasi 70% plastik: 30% pasir. Kata kunci: non-biodegradable, paving block, plastik, sampah